The Effect Of Constructing Wastewater Treatment Treatments (Wwtp) With Filtration Media For Reducing Bod5 And Cod Levels Of The Laboratory Wastewater Of The Poso Midwifery Study Program Poltekkes Kemenkes Palu - Marlina Fitriya Lailatul K; Lisda Widianti Longgupa; Khuzaifah Khuzaifah Khuzaifah (Labor Dasar dan Sentral Universitas Andalas, 2022)
The purpose of this study was to determine the effect of establishing wastewater treatment plant (WWTP) coupled with filtration media for decreasing levels of BOD5 and COD in laboratory wastewater. The research used quasi experimental method with one group pretest posttest design. The statistical test was used through the non-parametric test, namely Wilcoxon. The results showed that there was a decrease in the average COD level score before treated with the intervention, which was 144.515 (SD = 80.39). The the average COD level score after the intervention was 39.877 (SD = 22.236) with an average decrease of 104.638. Meanwhile, the average score of BOD5 levels before the intervention was 73.375 (SD = 41,505) and the average score after the intervention was 19,826 (SD = 11,539) with an average decrease of 53.549. The statistical test showed that there was a significant difference in between before and after the intervention with a value of 0.000 (p<0.05). Regarding to the obtained results,it can be concluded that there is an effect of making WWTP with filtration media on the reduction of BOD5 and COD levels of wastewater at the Poso Midwifery Laboratory of Poltekkes Kemenkes Palu